The Effects of Prednisone and Aspirin Administration on Pregnancy Outcomes in Mothers with RhD Isoimmunization and a History of Recurrent Pregnancy Loss: A Case Report - Susanty, Devi; Marhadisony, Regina; Indirayani, Ima; Aditya, Rizka; M Fuad (Journal of International Surgery and Clinical Medicine, 2025)
Introduction: Rhesus incompatibility arises when an Rh-negative mother becomes sensitized to the D antigen of an Rh-positive fetus, triggering the production of anti-D antibodies, a process known as isoimmunization. This condition is associated with severe obstetric complications, including Recurrent Pregnancy Loss (RPL) and Hemolytic Disease of the Fetus and Newborn (HDFN). Clinical management remains challenging, as no single therapeutic modality can comprehensively eliminate the adverse effects of isoimmunization. A targeted and integrated management approach is therefore imperative to optimize pregnancy outcomes. Emerging evidence suggests that corticosteroids combined with aspirin may confer beneficial effects in patients with rhesus incompatibility. Case Presentation: A 27-year-old woman, G5P0A4, with RhD-negative status, experienced recurrent pregnancy loss and was managed with prednisone (10 mg/day), aspirin, and Rh immunoglobulin (RhIg) at appropriate gestational intervals. The patient successfully carried the pregnancy to 36 weeks and six days, resulting in the birth of a healthy neonate. Discussion: Rhesus incompatibility is a clinically significant condition in which Rh-negative mothers develop isoimmunization following exposure to Rh-positive fetal blood, producing antibodies against fetal red blood cell antigens. This immunological response contributes to adverse pregnancy outcomes, most notably RPL and HDFN, both carrying substantial maternal and neonatal morbidity. Effective management continues to pose considerable clinical challenges due to limited therapeutic interventions capable of mitigating the immunological consequences of isoimmunization. Evidence from published case reports indicates that combined prednisone and aspirin administration may represent a promising adjunctive therapeutic strategy alongside RhIg prophylaxis. Conclusion: The integrated management incorporating RhIg prophylaxis as the cornerstone of therapy alongside adjunctive prednisone and aspirin was associated with a successful pregnancy outcome in this RhD-negative mother with a history of RPL. The relative contribution of each therapeutic component cannot be determined from a single case report. Further prospective studies with larger sample sizes are needed to evaluate the independent efficacy of corticosteroids and aspirin in this clinical context.